Variation [large type] - Yarros, Rebecca (Thorndike Press large print top shelf., 2024)
Elite ballerina Allie Rousseau is no stranger to pressure. With her mother's eyes always watching, perfection was expected, no matterthe cost. But when an injury jeopardizes all she's sacrificed for, Allie returns to her summer home to heal and recover. But the memories she's tried to forget rush in and threaten to take her under. As a Coast Guard rescue swimmer, Hudson Ellis knows that hesitation canmean the difference between life and death. He's always prided himself on being in the right place at the right time, especially when it came to Allie Rousseau--until the night he left for basic. After the biggest regret of his life, the secrets he keeps mean he can never be with the one woman he wants more than his next breath.